COVID-19 and ethical preparedness? - Druml, Christiane (Wiener Klinische Wochenschrift, 2020)
Summary Mankind has to prepare for a pandemic with respect to medical and practical aspects, but also with respect to ethical issues. There are various ethical guidelines for managing infectious disease outbreaks, but they do not apply to the specific aspects of the COVID-19 pandemic, since they were formulated after the different kinds of outbreaks of avian influenza and Ebola. Today we are confronted with completely new issues endangering our fundamental human rights. As COVID-19 is spreading all over the world, we are in a desperate situation to find treatment solutions; however, despite the urgency, scientific rules have to be applied as bad science is unethical since it might be harmful for patients. Fake news and alternative facts might not be easily recognized and are also threatening scientific values. Pandemics might be leading to a meltdown of the health system if no measures are being taken constraining fundamental human rights. Tracking of persons is violating human rights as well if not accepted on a voluntary basis. A failure to have safeguards for times of crisis leads to a scarcity of medicinal products and goods resulting in a nationalistic approach and ignorance of international solidarity. And last but not least selective measures and triage in intensive care have to be taught to young physicians and nursing staff in medical schools in order to be prepared in times of an infectious disease outbreak and scarcity of resources.